High blood pressure and maxillofacial surgeries - F. Jamali; P. Ghanbari (Tehran University of Medical Sciences, 1993)
This article is aimed to evaluate blood pressure changes in 100 patients (Normotensive and hypertensive) of dental clinics.  Blood pressure changes were recorded in particular stages: before surgery, 2 minutes after receiving local anesthesia, during surgery and 15 minutes post surgery. Results were analyzed via student paired T test to identify if there were any significant difference between two groups of normotensive and hypertensive and this was dangerous or significant enough to prohibit patients from receiving dental treatments.